Synergistic use of Sentinel-1A/B, TanDEM-X and COSMO-SkyMed for Cryosphere science - Milillo, Pietro; Moreira, Alberto; Zink, Manfred; Milillo, Giovanni; Rignot, Eric; Rizzoli, Paola; Scheuchl, Bernd; Mouginot, Jeremie; Bueso Bello, Jose Luis; Prats, Pau (2019)
We employ data from the second generation of SAR systems, e.g., the Italian COSMO-SkyMed (CSK) constellation, the German TanDEM-X formation and the European Sentinel-1A/B constellation to monitor the characteristics of grounding line migration using short repeat-time interferometry and accurate InSAR DEM in the Amundsen Sea Embayment (ASE), West Antarctica. The ASE is a marine-based ice sheet with a retrograde bed containing enough ice to raise global sea level by 120 cm. Several studies have inferred the mechanical properties of portions of ASE using observationally constrained numerical models, but these studies offer only temporal snapshots of basal mechanics owing to a dearth of observational time series. Prior attempts of grounding lines mapping have been limited because few space-borne SAR missions offer the short-term repeat pass capability required to map the differential vertical displacement of floating ice at tidal frequencies with sufficient detail to resolve grounding line boundaries in areas of fast ice deformation. Using 1-day CSK repeat pass data and TanDEM-X DEMs, we collected frequent, high-resolution grounding line measurements of Pine Island (PIG), Thwaites, Kohler and Smith glaciers spanning 2015-2016. We compare the results with ERS data spanning 1996-2011, and Sentinel-1A 2014-2015 data. We observe an ongoing, rapid 2 km/yr grounding line retreat on Smith, 0.5 km/yr retreat on Pope, ongoing 1 km/yr retreat on Thwaites and PIG and a slight re-advance on Kohler since 2011. On PIG, the data reveal rapid subsidence along the glacier flanks, significantly more than in 1996/2000. We do not observe similar patterns on the other glaciers.